The Potential Of hBN Nanoparticles As Friction Modifier And Antiwear Additive In Engine Oil - Abdullah, Muhammad Ilman Hakimi Chua; Abdollah, Mohd Fadzli; Amiruddin, Hilmi; Tamaldin, Noreffendy; Mat Nuri, Nur Rashid (EDP Sciences, 2016)
-